2008
DOI: 10.1517/17425255.4.2.151
|View full text |Cite
|
Sign up to set email alerts
|

The use of hepatocytes in evaluating time-dependent inactivation of P450in vivo

Abstract: Factors that may impact prediction accuracy, such as nonspecific binding, metabolism of inactivator, active transport, and sequential inhibitory metabolites, can be assessed by performing 'in vitro-in vitro' correlation between microsomes and hepatocytes. Together with microsomal data and the aid of computer modeling and simulation, hepatocytes provide a powerful tool to optimize the integrated approaches aimed at quantitatively predicting TDI in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…This may be a result of varying contributions of the three points listed above for each inactivator. These observations are consistent with those of Zhao (2008), who showed differing inactivation potency (time-dependent inactivation IC 50 ) between HLMs and suspended human hepatocytes for amprenavir and erythromycin but not for diltiazem, raloxifene, or troleandomycin. This finding highlights the importance of using SCHHs to determine CYP3A inactivation because this model includes the canalicular efflux processes that may determine intracellular drug concentrations.…”
Section: Downloaded Fromsupporting
confidence: 92%
“…This may be a result of varying contributions of the three points listed above for each inactivator. These observations are consistent with those of Zhao (2008), who showed differing inactivation potency (time-dependent inactivation IC 50 ) between HLMs and suspended human hepatocytes for amprenavir and erythromycin but not for diltiazem, raloxifene, or troleandomycin. This finding highlights the importance of using SCHHs to determine CYP3A inactivation because this model includes the canalicular efflux processes that may determine intracellular drug concentrations.…”
Section: Downloaded Fromsupporting
confidence: 92%
“…The ideal in vitro system for comprehensively evaluating drug-drug interactions should theoretically be human hepatocytes (Zhao, 2008), given the full complement of metabolic clearance mechanisms. Even though the ability to conduct in vitro DDI studies has been demonstrated in human hepatocyte suspensions (Mao et al, 2011), there are limitations with the long-term viability and enzymatic activity of the cells in suspension (Zhao, 2008). It has been demonstrated that human plated cell systems offer unique advantages over human cell suspensions for time-dependent inhibition studies (Li and Doshi, 2011).…”
Section: Albaugh Et Almentioning
confidence: 99%
“…The process of using in vitro inactivation data to estimate and rank order the DDI potential of compounds is well established (Mayhew et al, 2000;Obach et al, 2006Obach et al, , 2007, and the in vitro inactivation kinetic parameters along with the in vivo systemic and intestinal concentration of the time-dependent inhibitor, fraction metabolized, and intestinal extraction ratio of the victim probe drug, and enzyme degradation rates (Correia, 1991;Greenblatt et al, 2003;Ghanbari et al, 2006) are used to estimate the potential for a clinical DDI (Obach et al, 2006(Obach et al, , 2007. However, precipitants of TDI are not always products of oxidative metabolism (Ogilvie et al, 2006;Baer et al, 2009;Xu et al, 2009;Honkalammi et al, 2011), and therefore it may be more relevant to assess TDI in a system containing the full complement of drug-metabolizing enzymes, such as hepatocytes (Li, 1997;Zhao et al, 2005;Zhao, 2008;Li and Doshi, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated hepatocytes are used to determine many properties of a candidate drug, its intrinsic clearance (CL int ), and metabolic pathways, and increasingly also to assess drug-drug interactions mediated by drug-metabolizing enzymes and/or drug transporters (Soars et al, 2007a(Soars et al, , 2009Zhao, 2008;Chiba et al, 2009;McGinnity et al, 2009;Brown et al, 2010;Giacomini et al, 2010).…”
Section: Introductionmentioning
confidence: 99%